Interactive formulas in managing the budget of commercial banks - Bashar Thanoun; Hassan Sobhi (Iraqi Journal for Administrative Sciences, 2024)
Managing the commercial bank budget is not a new matter for banking institutions, as, without this matter, it is not expected that any of these institutions would have continued over the years without giving a reasonable amount to this issue in one form or another. A closer look at the composition of commercial banks' assets and liabilities during the last decades of the last century clearly shows the important change in commercial banks' management policy. They are reflections of the rapid fluctuations in the economic environment, technological development, and intense competition between financial institutions, including commercial banks. The management of commercial banks also realized their inability to market their traditional products, which was reflected in the limited profits. For this reason, commercial banks sought to coexist with developments in the world of finance and banking within the framework of what is known as financial engineering, which proposed a set of innovative financial tools whose application helps to hedge risks and increase risks—Bank profitability according to advanced interactive formulas in managing the commercial bank budget.